Prevalência e incidência de dor lombar e fatores associados em estudantes do ensino médio: um estudo longitudinal - Bento, Thiago Paulo Frascareli (2019)
Introduction: Low back pain has a high prevalence and incidence in the economically active population, children and adolescents, being the main cause of physical disability among adults of all ages. Objectives: 1) To determine the prevalence and incidence of low back pain in young high school adolescents and the change in these responses over a period of twelve months. 2) Check the factors associated with high intensity and high frequency of low back pain in high school students. 3) To analyze the association between low back pain and individual variables, sociodemographic, sedentary activities, level of physical activity, psychosocial and the change in these responses in a period of twelve months. Methods: A study was conducted with 1628 high school students from public schools in the city of Bauru / SP, evaluated in two moments (initial and after twelve months). The following instruments were used to collect data: 1. Characterization of participants (demographic, socioeconomic aspects), use of electronic devices (TV, computer, tablet and cell phone); 2. Questionnaire on Capacities and Difficulties; 3. Baecke's questionnaire; 4. Musculoskeletal symptoms through the Nordic questionnaire. Descriptive and bivariate and multivariate logistic regression analyzes were used. Results: The overall prevalence of low back pain was 46.7% (CI 44.27 to 49.11), with men presenting a prevalence of 42.0% (CI 36.63 to 43.41) and women 58.0% (CI 49.73 to 56.51), with a statistically significant difference. The variables that remained significantly associated with low back pain were: female (RP = 1.70), time of use of the TV above 3 hours per day (RP = 1.17), portable computer use (RP = (RP = 1.23), use of the cell phone in the posture (RP = 1.49), cell phone usage time over 3 hours per day (RP = 1 , 36), tablet use (RP = 1.67) and tablet usage time over 3 hours per day (RP = 1.46). The low frequency and the high intensity had a greater proportion among those with low back pain. The variables that remained significantly associated with the high frequency of low back pain were women, posture lying in the use of the tablet, time of daily use of the tablet, use of computer, time of daily use in the cell phone and amount of hours of TV / day , while female, computer use, daily use time of the cell phone and amount of TV hours per day with the high intensity of low back pain. The cumulative incidence of pain was 18.9% (95% CI: 16.2 - 21.8), 14.8% (95% CI: 11.7 - 18.5) in men and 24.1% (95% CI: %: 19.8 - 28.9) in women. The variables that remained significantly associated with the incidence of low back pain were: female sex (RR = 1.78), sitting tablet use (RR = 4.34), daily tablet time (RR = 3.21) (RR = 1.49), posture lying in the cell phone (RR = 1.49) and depressive symptoms (RR = 2.81). Conclusion: There was a high prevalence and incidence of low back pain in adolescents. The factors associated with the prevalence of low back pain, high frequency, high intensity and pain incidence were sociodemographic variables, use of electronic equipment and depressive symptoms.